Study the photocatalysis activity of hydrothermal-synthesized BiVO4–graphene composite on methylene blue. Issue 14 (21st March 2016) - Cai, Xiang; Zhang, Bing; Shi, Lei; Liu, Huidi; Zhang, Jinglin; Huang, Langhuan; Tan, Shaozao
Abstract: A hydrothermal synthesis method was developed to prepare graphene-supported bismuth vanadate (BiVO4 ) particle (BiVO4 –graphene) using graphene oxide, Bi(NO3 )3 ·5H2 O, and NH4 VO3 as raw materials. The composite was characterized by various analytical methods, including X-ray powder diffraction, Fourier transform infrared spectroscopy, diffuse reflection spectra, transmission electron microscope, X-ray photoelectron emission spectroscopy, and fluorescence spectra. The photocatalytic activity of BiVO4 – graphene composite was investigated by the degradation of methylene blue in an aqueous solution under visible light irradiation. It had been confirmed that the presence of graphene enhanced the photocatalytic activity of BiVO4 particle, and the BiVO4 –1.0% graphene showed the best photocatalytic activity. The improved visible light activity of BiVO4 –graphene was due to the enhancement of electron–hole separation by the electron trapping of graphene. Also, a possible mechanism was proposed to elucidate the role of graphene in BiVO4 –graphene composite as a photocatalyst for degradation of organic pollutant.